A Sustainable, Semi‐Continuous Flow Synthesis of Hydantoins. Issue 38 (7th July 2016) - Vukelić, Stella; Koksch, Beate; Seeberger, Peter H.; Gilmore, Kerry
Abstract: Hydantoins are an important class of heterocycles with applications in pharmacy, agriculture, and as intermediates in organic synthesis. Traditional synthetic procedures to access hydantoins are target oriented with multiple synthetic steps and often use reagents that are not commercially available or sustainable. Herein, an efficient process is described for accessing hydantoins starting from commercially available amines using consecutive gas–liquid transformations (oxygen, carbon dioxide). This semi‐continuous process produced ten benzylic/aliphatic hydantoins in good overall yields (52–84 %). Abstract : Let it flow ! A new process for the synthesis of hydantoins, starting from commercially available amines using consecutive gas–liquid transformations, has been described. The semi‐continuous process uses highly atom economical and traceless reagents (O2, CO2, light) in environmentally friendly solvents (MeOH and MeTHF) and produces ten benzylic/aliphatic hydantoins in good overall yields (52–84 %) without need for further chromatographic purifications.